Solve for y 2(-1)+3y=-10

Math
2(-1)+3y=-10
Multiply 2 by -1.
-2+3y=-10
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 2 to both sides of the equation.
3y=-10+2
Add -10 and 2.
3y=-8
3y=-8
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3y=-8 by 3.
3y3=-83
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3y3=-83
Divide y by 1.
y=-83
y=-83
Move the negative in front of the fraction.
y=-83
y=-83
The result can be shown in multiple forms.
Exact Form:
y=-83
Decimal Form:
y=-2.6‾
Mixed Number Form:
y=-223
Solve for y 2(-1)+3y=-10

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top